After Markets: Researching Hybrid Arrangements - McGoey, L; Marres, N (2010)
This workshop, organised by InSIS, aimed to foster an exchange between different approaches in science and technology studies and political and economic sociology about the study of heterogeneous arrangements – assemblages in which economic relations are always entangled with political, technical, ethical, social and material ones. We ask how this research can engage with the current context, in which the ‘free market’ is becoming a less secure and more openly contested category.